Imalah Dan Taqlil: Studi Qira’ah Sab`Ah Kitab Fayḍu Al-Barakāt Fī Sab`I Al-Qirā’at - Farhan Nasrullah, Mohammad (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
The Qur'an was revealed to the Arabs according to their dialect. This is so that they can interact with the Qur'an in accordance with their respective dialects until there are seven valid Qira'ah of the Qur'an (Qira'ah Sab'ah). As a Qira’ah Mutawatiroh, Qira'ah Sab'ah has its own Qira'ah differences, especially in terms of foreign readings (gharib). Among the most common gharib readings found in Qira'ah Sab'ah are those related to Imalah (Imalah Kubro) and Taqlil (Imalah Sughra). This research will explore how the reading of Imalah and Taqlil from the point of view of Qira'ah Sab'ah based on the book of Qira'at Ulama Nusantara, namely Kitab Fayḍu al-Barakāt fī Sab`i al-Qirā'at by KH Muhammad Arwani Amin al-Qudsy (Kudus). This research uses qualitative research methods with literature (library research) and the approach used for data analysis is content analysis. The primary data source used in this research is the Book of Fayḍu al-Barakāt fī Sab`i al-Qirā'at and other Qira'at Books. While secondary data sources use books or journals relevant to this research. This study resulted in the findings that Qira'ah Hamzah and Ali al-Kisa'i are the Qira'ah that uses Imalah the most, Qira'ah Shu'bah uses a lot of Imalah on muqhatho'ah surah such as Alif lam Ra’, Qira'ah Ibn Amir uses little Imalah, Qira'ah Hafs only uses Imalah in Surah Hud verse 41, Qira'ah Qolun only uses a little Taqlil, Qira'ah Warsy uses a lot of Taqlil and only Imalah on the letter ha verse Ṭāḥā, Qira'ah Abu Amr sometimes uses Imalah and Taqlil, and Qira'ah Ibn Kathir is the only Qira'ah that does not use Imalah and Taqlil.